2018
DOI: 10.1136/bmj.k119
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular outcomes associated with canagliflozin versus other non-gliflozin antidiabetic drugs: population based cohort study

Abstract: ObjectiveTo evaluate the cardiovascular safety of canagliflozin, a sodium-glucose cotransporter 2 inhibitor for the treatment of type 2 diabetes mellitus, in direct comparisons with DPP-4 inhibitors (DPP-4i), GLP-1 receptor agonists (GLP-1RA), or sulfonylureas, as used in routine practice.DesignPopulation based retrospective cohort study.SettingNationwide sample of patients with type 2 diabetes from a large de-identified US commercial healthcare database (Optum Clinformatics Datamart).ParticipantsThree pairwis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
196
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 150 publications
(221 citation statements)
references
References 24 publications
23
196
2
Order By: Relevance
“…To address this in our study, we employed an incident new‐user design and we censored follow‐up when patients switched from one drug to another. Two other recent analyses of real‐world data reported findings similar to those of our study …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…To address this in our study, we employed an incident new‐user design and we censored follow‐up when patients switched from one drug to another. Two other recent analyses of real‐world data reported findings similar to those of our study …”
Section: Discussionsupporting
confidence: 92%
“…Several observational studies have recently evaluated the cardiovascular safety of SGLT2 inhibitors among patients with type 2 diabetes . One population‐based study, which used data from the Health Improvement Network database, found that, compared to use of other glucose‐lowering agents, the use of empagliflozin was associated with lower risk of all‐cause mortality, irrespective of baseline CVD .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sodium‐glucose co‐transporter‐2 (SGLT2) inhibitors—a newer class of antidiabetic medications—reduce plasma glucose in an insulin‐independent manner by inhibiting glucose reabsorption in the proximal tubule . In addition to reducing serum glucose concentration, SGLT2 inhibitors also exert additional beneficial effects on cardiovascular markers including blood pressure and body weight, cardiovascular endpoints and all‐cause mortality …”
Section: Introductionmentioning
confidence: 99%
“…However, patients with T2D and a broad CV risk profile enrolled in DECLARE experienced significant reductions in the composite of CV death or heart failure hospitalizations when treated with dapagliflozin compared with placebo . Further supporting these findings from CVOTs, the CVD‐REAL 1 and 2 studies, as well as other real‐world studies, also found a significantly lower risk of CV events associated with initiation of an SGLT‐2i (vs other glucose‐lowering agents). Although large pharmacoepidemiologic studies such as CVD‐REAL have potential limitations (including a possibility of residual confounding), their findings are important and complementary to randomized controlled trials, as they include a population of patients with T2D that is much more representative of that seen in routine clinical practice, with a much broader CV risk profile (13‐25% of patients had prior CVD in CVD‐REAL) …”
Section: Discussionmentioning
confidence: 69%